Penggunaan Teknologi Biofloc pada Budidaya Perikanan terhadap Peningkatan Produksi : Studi Literatur - Hafiz Rahmansyah Yusup; Amelia Setiawan; Hamfri Djajadikerta (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Biofloc Technology (BFT) has emerged as a transformative innovation in aquaculture to address challenges in food security, production efficiency, and environmental sustainability. This literature study evaluates the impact of BFT on survival rates, growth performance, economic benefits, and environmental sustainability across various countries. Research results demonstrate that BFT improves fish survival rates by 20-30% through enhanced water quality management and provision of microbial-based natural feed, while reducing dependence on commercial feed by 15-20%. Economically, BFT reduces operational costs through feed efficiency (lowered FCR) and decreased water exchange expenses, while increasing farmers' profits. From an environmental perspective, BFT implementation enables nutrient recycling and waste reduction, while minimizing water exchange, thereby lessening negative environmental impacts. However, implementation challenges in Indonesia remain related to technical execution and farmers' understanding, contrasting with developed countries that have advanced automation and industrial integration. Strategic recommendations include establishing standardized protocols, continuous training programs, and financial support schemes to optimize BFT's contribution toward achieving sustainable development goals (SDGs) in the fisheries sector.